Effectiveness of one-stop integrated services in optimizing the role of Indonesian migrant workers protection agency in Central Java - Shalihah, Fithriatus; Agusmidah, Agusmidah; Wijayanti, Asri (Linguistics and Culture Review, 2021)
This study aims to determine the application of an integrated service system in several Central Java districts to protect Indonesian workers. This research uses the observational method. This study involved seven districts contributing to Indonesian workers in the province of Central Java. The sample districts include Banyumas, Cilacap, Pati, Kendal, Sragen, Grobogan and Wonosobo. The data were obtained utilizing field observations, interviews, quinones and literature studies, analyzed using the Miles and Huberman models, namely data reduction, data tabulation, data presentation and conclusion drawing. The study results show that the One-Stop Integrated Service also helps reduce Illegal Indonesian Migrant Workers and prevents document falsification. Limited Human Resources (HR) who can act as operator staff at LTSA office outlets are also a factor in the ineffectiveness of the One-Stop Integrated Service. This means that the presence of LTSA in various districts/cities in Central Java can facilitate the role of BP2MI in carrying out its functions. However, it cannot run effectively as a whole.